2009
DOI: 10.1111/j.1600-0765.2008.01130.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Porphyromonas gingivalis infection on cytokine levels in type 2 diabetic mice

Abstract: These observations suggest that tumor necrosis factor-alpha, interleukin-6 and adiponectin are an integral part of the link between diabetes mellitus and Porphyromonas gingivalis infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 36 publications
1
29
0
3
Order By: Relevance
“…The alteration in serum levels of adiponectin according to periodontal status and the effect of adiponectin on periodontopathogen-induced cytokine expression by macrophages and osteoclast formation have been estimated [23-25], but few studies have addressed the effect of adiponectin on the cells of periodontal tissue such as PDL and gingival fibroblasts. In this study, it was shown that PDL and gingival fibroblasts express AdipoR1 and that gAd does not affect the production of IL-6 and IL-8 in those cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The alteration in serum levels of adiponectin according to periodontal status and the effect of adiponectin on periodontopathogen-induced cytokine expression by macrophages and osteoclast formation have been estimated [23-25], but few studies have addressed the effect of adiponectin on the cells of periodontal tissue such as PDL and gingival fibroblasts. In this study, it was shown that PDL and gingival fibroblasts express AdipoR1 and that gAd does not affect the production of IL-6 and IL-8 in those cells.…”
Section: Discussionmentioning
confidence: 99%
“…One study found a trend toward decreased serum levels of adiponectin in periodontitis patients [22]. Moreover, infection with periodontopathogen such as Porphyromonas gingivalis was shown to cause decreased serum levels of adiponectin in type 2 diabetic mice [23]. In another study, antimicrobial periodontal treatment (APT) not only ameliorated periodontitis but also increased serum levels of adiponectin in type 2 diabetes mellitus patients.…”
Section: Introductionmentioning
confidence: 99%
“…The authors postulated that glycaemic control in patients with periodontitis and diabetes is potentially influenced by the persistence of P. gingivalis, particularly clones with type II fimbriae, following treatment (Makiura et al 2008). It has also been reported in in vitro studies that cytokine induction (specifically IL-1b, IL-8, IL-12 and TNF-a) by P. gingivalis with type II fimbriae is greater than that induced by P. gingivalis with type I fimbriae (Sugano et al 2004), and in animal studies that P. gingivalis inoculation can lead to elevated serum levels of TNF-a and IL-6 (Nishihara et al 2009). Clearly, more research is required, integrating both microbial assessment and analysis of serum cytokine levels.…”
Section: Microbial Factorsmentioning
confidence: 94%
“…A number of studies of animal models have highlighted the importance of TNF-a in possibly prolonging the immune response to plaque bacteria in both T1DM and T2DM and thereby promoting periodontitis in these conditions (Lalla et al 2000a,b, Graves et al 2004, Naguib et al 2004, Liu et al 2006a,b, Watanabe et al 2008, Pacios et al 2012. The role of TNF-a (and IL-6) in the enhanced immune responses to periodontal bacteria in diabetic mouse models has also been highlighted (Graves et al 2005, Nishihara et al 2009, Takano et al 2010). However, evidence for any association between levels of TNF-a in oral fluids or gingival tissues and T2DM in chronic periodontitis is inconsistent (Duarte et al 2007b, Navarro-Sanchez et al 2007, Ross et al 2010, Santos et al 2010b.…”
Section: Cytokines and Adipokinesmentioning
confidence: 99%
“…), and in animal studies that P. gingivalis inoculation can lead to elevated serum levels of TNF‐α and IL‐6 (Nishihara et al. ). Clearly, more research is required, integrating both microbial assessment and analysis of serum cytokine levels.…”
Section: The Impact Of Periodontal Disease On Diabetesmentioning
confidence: 99%